L’éducation au politique à travers les questions environnementales : ancrages épistémologiques et alignement avec l’éducation au développement durable - Melki Slimani (Éducation et Socialisation)
Political learning related to environmental issues is diffused among the so-called ’educations for’. It is also at the crossroads of different informal, formal and non-formal educational logics. The consequence is the combined epistemological and pedagogical fragility of such learning. This article addresses the need for epistemological and pedagogical anchors to support the construction of appropriate curricula for political education through environmental issues. In the first part, political learning is formalised according to an epistemological perspective that considers it as a process of production of political knowledge. Then, in a second part, pedagogical anchors are explored in terms of possible productive relationships between political learning and the learning objectives of education for sustainable development.